The association between age of first exposure to american football at a young age and later-life health issues in healthy, community-dwelling adults - Rigney, G. H.; Dugan, J. E.; Bishay, A.; Jonzzon, S.; Jo, J.; Williams, K. L.; Zuckerman, S. L.; Terry, D. P. (Sports Medicine, 2025)
Introduction: Younger age of first exposure (AFE) to American Football (football) is associated with later-life health problems among former professional athletes in several studies; however, studies examining amateur (i.e., nonprofessional) athletes are less clear. Objective: In a cohort of former amateur American Football players, this study assessed whether AFE to football was associated with: (1) psychiatric and neurobehavioral symptoms, (2) cognitive difficulties, (3) general health problems, (4) motor symptoms, and (5) functional status. Methods: A cross-sectional survey study was conducted using the ResearchMatch platform. The key independent variable was age of first exposure to football (AFE < 12 versus AFE = 12). Main outcomes included depressive symptoms (Patient Health Questionnaire-9; PHQ-9), anxiety symptoms (Generalized Anxiety Disorders-7; GAD-7), cognitive difficulties (British Columbia Cognitive Complaints Inventory; BC-CCI), Neurobehavioral Symptom Inventory (NSI) score, and prevalence of other health problems. Multivariable regressions were assessed for associations between AFE and outcome variables. Results: In total, 107 male participants with exposure to football (mean age: 60.6 ± 15.1 years) reported an average of 4.2 ± 2.7 years of exposure to football, with an average AFE of 11.7 ± 3.1 years. In multivariable analyses, AFE < 12 was not a significant predictor of PHQ-9 (unstandardized beta, B: 0.51, standard error, SE: 1.25, p = 0.682), GAD-7 (B: 0.09, SE: 0.95, p = 0.926), NSI (B: - 0.56, SE: 2.93, p = 0.850), or BC-CCI (B: - 0.65, SE: 0.77, p = 0.403). However, more prior concussions were associated with worse PHQ-9 (B: 0.44, SE: 0.10, p < 0.001), GAD-7 (B: 0.33, SE: 0.07, p < 0.001), NSI (B: 1.04, SE: 0.23, p < 0.001), and BC-CCI scores (B: 0.26, SE: 0.06, p < 0.001). AFE < 12 did not predict general health problems or independent functional status. Conclusions: AFE to football was not associated with adverse psychiatric, cognitive, neurobehavioral, or general health outcomes among young, former amateur American Football players. However, more lifetime concussions were associated with adverse cognitive and psychiatric health outcomes. Future studies should examine similar outcomes in older cohorts with more comorbidities to further minimize potential confounding between general health and lack of later-life symptoms.